Frequency of Common Bacterial Organisms in Neonatal Sepsis in a Tertiary Care Centre - Sana Nafis, Sohail Akhtar, Furqan Ahmad, Ghulam Hussain, Fazal Badshah, Izhar Ali, Sara Ahmad, Faiza, Azaz Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study goal is to determine the frequency of various bacterial organisms in neonatal sepsis and to know the sensitivity pattern of these organisms to the commonly used antibiotics. Methods: After the ethical approval from institutional review board, this descriptive cross-sectional study was conducted at Neonatal Intensive Care Unit of Medical Teaching Institute, Lady Reading Hospital Peshawar from Feb 5, 2020 to Aug 4, 2020. Through non-probability consecutive sampling 162 neonates between from 1st day to 28 days of life, of either gender, or gestational age of <28 weeks were included in the present study. The patient’s age, gender, gestational age, birth weight, and delivery method were noted, as well as a thorough account of their current medical condition, their signs and symptoms, and any prior hospitalizations or procedures were recorded in a Performa. Results: In this study, 162 malno children presenting with neonatal Sepsis were included. Male to female ratio was 1:0.61. The study included age ranged from 3 up to 28 days. Average age was 6.7+6.48 days. Staphlyococcus aureus was found in majority of cases which is 72(44.4%), followed by Klebsiella in 59(36.4%), Escherichia Coli in 48(29.6%), streptococci is found in 33(20.4%) children while 44(27.2%) patients have Coagulase negative staphylococci. Amikacin, amoxicillin, Cefotaxime, Imipenem and Linezolid give the same pattern as that of co-trimoxazole. Conclusion: Babies with septic shock have undergone culture and sensitivity testing. In addition to aiding in patient care, this would also inhibit the unnecessary use of antibiotics and forestall the escalation of newborn sepsis. Keywords: C-reative protein, Neonates, Neonatal Sepsis.